Elaboration of the Independent Waste in the Circular Economy Based on Disapu Application - Asyari, Hasyim; Majid, Mohammad Dzul Arsyl; Saifullah, Muhamad Farizqi; Hapsari, Ayu Titi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Purworejo Village is one of the villages in Senduro District, Lumajang Regency, East Java Province. The village is facing significant waste management problems, most villagers are still lagging behind in environmental management, especially in waste management which still applies the KAB (Collect - Transport - Dump) pattern. This Community Service Program aims to invite the community to apply the 3R pattern (reduce, reuse, recycle) in processing household waste and educate the community with the support of technology developed based on web apps as an educational media and to overcome these problems. With the hope of increasing public awareness of the importance of managing waste, facilitating the waste sorting process, and encouraging the use of organic waste into liquid organic fertilizer and animal feed. The results of this community service are the formation of an application called Digital Sampah Purworejo (DISAPU) as an effective digital waste bank management media in organizing waste collection, increasing the economic value of waste, and the Independent Waste Community (MAMARISA) program receiving support. The implementation methods used in this community service are problem identification, solution formulation and program planning, training and mentoring, monitoring and evaluation of program sustainability.